The alteration of the sensorimotor network in trigeminal neuralgia after microvascular decompression surgery: a follow-up study using independent component analysis - Zhang, Yan; Wang, Xueju; Wang, Xuefeng; Huang, Gengdi (Frontiers in Physiology, 2025)
IntroductionTrigeminal neuralgia (TN) is a chronic neuropathic pain disorder characterized by spontaneous or triggered electric shock-like facial pain. Microvascular decompression (MVD) is the most effective surgical intervention for classical TN that is refractory to medication. Recent advances in neuroimaging have enhanced visualization of the trigeminal nerve’s vascular anatomy, deepening insights into TN pathophysiology and paving the way for improved diagnostics and therapies. Resting-state functional magnetic resonance imaging (rs-fMRI) has been extensively applied in studies of TN, uncovering alterations in brain activity, functional connectivity, cortical thickness and neural networks.MethodsIndependent component analysis (ICA) presents a powerful alternative for analyzing fMRI data, offering several advantages over traditional region of interests (ROIs) approaches. The sensorimotor network playing a key role in pain modulation, identifying neuroimaging differences in the sensorimotor network is crucial for detecting and intervening in TN, Forty TN patients underwent MVD surgery, with follow-up assessments conducted 6 months postoperatively and twenty-five healthy controls (HC) were recruited and scanned with resting state fMRI (rs-fMRI). Group ICA was used to identify ROIs and assessed inter-group differences in neural activity using false discovery rate (FDR) correction.ResultsCompared to the HC, increased activity was observed in the right frontal operculum cortex, right insular cortex, right inferior frontal gyrus (pars opercularis), and right frontal pole in TN patients. Conversely, decreased activity was found in the right cerebellum (lobule IX) and left cerebellum (lobules VIII and IX). Compared to the pre-surgery, increased activity was found in the right precentral gyrus in the post-surgery group. Compared to the HC, long-term increased activity was still present in the right frontal operculum cortex, right insular cortex, right inferior frontal gyrus (pars opercularis), and right frontal pole despite the effectiveness of MVD surgery. In contrast, MVD significantly reduced the area of aberrant activation regions, particularly in the operculo-insular cortex, and also normalized cerebellar abnormalities.DiscussionOur study demonstrates that ICA can effectively identify distinct patterns of functional connectivity in the sensorimotor network associated with TN and MVD surgery. These regions are involved in altered pain processing, including nociceptive stimulus integration, subjective pain perception, pain chronification, and pain-related empathy. Our findings suggest promising biomarkers for TN and provide insights for developing targeted treatments.